Anthropometric measurements and lipid profiles to detect early lipodystrophy in antiretroviral therapy experienced HIV-infected children in the CHAPAS-3 trial. - Musiime, V; Cook, A; Kayiwa, J; Zangata, D; Nansubuga, C; Arach, B; Kenny, J; Wavamunno, P; Komunyena, J; Kabamba, D; Asiimwe, A; Mirembe, G; et al. (2014)
BACKGROUND: Few studies have investigated objective markers of lipodystrophy in African children. We compared body circumferences, skin-fold thickness (SFT) and lipids in antiretroviral therapy (ART)-naive and stavudine (d4T)-exposed children with HIV-uninfected controls. METHODS: In the CHAPAS-3 trial, HIV-infected children (ART-naive or on d4T for ≥2 years without clinical lipodystrophy) were randomized to d4T, abacavir or zidovudine with lamivudine (3TC) plus a non-nucleoside reverse transcriptase inhibitor. Mid-upper-arm circumference (MUAC) and calf circumference (CC), SFT (biceps, triceps, sub-scapular and supra-iliac) and fasting lipids (total cholesterol [TC], low-density lipoprotein [LDL], high-density lipoprotein [HDL] and triglycerides [TRIG]) were measured at randomization in all HIV-infected children, and in HIV-uninfected controls. Age- and sex-adjusted z-scores of MUAC, CC, SFT and the sum of SFT (SSF) using Dutch reference data were compared across groups using linear regression. RESULTS: Of 496 children, 49% were male, 299 (median age 2.5 years [IQR 1.5-4.0]) were ART-naive, 109 (median age 6 years [IQR 5.5-7.0]) were ART-experienced and 88 (median age 2.2 years [IQR 1.5-3.0]) were control children. Overall, 100% and 95% of ART-experienced children had been on d4T plus 3TC and nevirapine, respectively, for a median 3.5 years (IQR 2.6-4.2). Mean (sd) weight-for-age z-scores and MUAC z-scores were -1.51 (1.29) versus -0.90 (0.88) versus -0.33 (1.15) and -1.56 (1.25) versus -1.24 (0.97) versus -0.65 (1.06) in ART-naive versus -experienced versus controls, respectively (all P<0.02). The mean (sd) of SSF was lower in the ART-experienced (-0.78 [1.28]) than in the ART-naive (-0.32 [1.09]; P<0.0001) children and controls (-0.29 [0.88]; P<0.002). ART-experienced children had higher mean fasting TC, LDL and HDL but lower TRIG compared to ART-naive children (P-values <0.0001), and higher TC and HDL but lower TRIG compared to controls (P-values <0.01). CONCLUSIONS: In ART-experienced children on d4T-containing regimens, we observed lower SFT and higher TC and LDL values compared to ART-naive children and HIV-uninfected controls.